2021
DOI: 10.1161/atvbaha.121.316324
|View full text |Cite
|
Sign up to set email alerts
|

Causal Associations Between Blood Lipids and COVID-19 Risk: A Two-Sample Mendelian Randomization Study

Abstract: Objective: Coronavirus disease 2019 (COVID-19) is a global pandemic caused by the severe acute respiratory syndrome coronavirus 2. It has been reported that dyslipidemia is correlated with COVID-19, and blood lipids levels, including total cholesterol, HDL-C (high-density lipoprotein cholesterol), and LDL-C (low-density lipoprotein cholesterol) levels, were significantly associated with disease severity. However, the causalities of blood lipids on COVID-19 are not clear. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 58 publications
0
17
1
1
Order By: Relevance
“…Mendelian randomization studies have explored the role of a wide range of anthropometrics and biomarkers in COVID-19 risk, including anthropometrics, blood pressure, coagulation factors, cytokines, inflammatory markers, glycaemic traits, haematological traits, lipids, liver functions, renal functions and vitamins. 27 , 31–33 , 35 , 38–40 , 42 , 44–47 , 49 , 52 , 53 , 55 , 58–60 , 62 , 64 , 65 Consistent evidence suggested that obesity [higher body mass index (BMI) and trunk fat ratio] was associated with higher COVID-19 risk 27 , 32 , 38 , 42 , 45 , 53 and one study also showed that increase in height was associated with higher risk of COVID-19 susceptibility. 27 Consistent evidence showed systolic and diastolic blood pressure to have no role in COVID-19 risk, 27 , 32 , 42 , 49 , 53 although one study found that higher pulse pressure was associated with higher risk of COVID-19 hospitalization in people of mixed ancestry but not of European ancestry.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Mendelian randomization studies have explored the role of a wide range of anthropometrics and biomarkers in COVID-19 risk, including anthropometrics, blood pressure, coagulation factors, cytokines, inflammatory markers, glycaemic traits, haematological traits, lipids, liver functions, renal functions and vitamins. 27 , 31–33 , 35 , 38–40 , 42 , 44–47 , 49 , 52 , 53 , 55 , 58–60 , 62 , 64 , 65 Consistent evidence suggested that obesity [higher body mass index (BMI) and trunk fat ratio] was associated with higher COVID-19 risk 27 , 32 , 38 , 42 , 45 , 53 and one study also showed that increase in height was associated with higher risk of COVID-19 susceptibility. 27 Consistent evidence showed systolic and diastolic blood pressure to have no role in COVID-19 risk, 27 , 32 , 42 , 49 , 53 although one study found that higher pulse pressure was associated with higher risk of COVID-19 hospitalization in people of mixed ancestry but not of European ancestry.…”
Section: Resultsmentioning
confidence: 96%
“… 27 There is suggestive evidence showed that haematological traits (higher basophil count, basophil percentage of white cells, lymphocyte count, myeloid white cell count, neutrophil count, red blood cell count, white blood cell count and lower mean corpuscular haemoglobin) were associated with reduced risk of COVID-19 severity and hospitalization. 27 , 58 , 59 Evidence was inconsistent for lipids with risk of COVID-19, 27 , 32 , 39 , 42 , 53 , 55 , 62 , 65 where some suggested that higher low-density lipoprotein (LDL)-cholesterol, 32 , 42 small very LDL cholesterol (VLDL) particles, 55 apolipoprotein B, 62 total cholesterol and total cholesterol in medium VLDL 55 , 62 and triglycerides 27 , 62 were associated with higher risk of COVID-19 whereas others suggested null association. 27 , 32 , 39 , 42 , 53 , 62 , 65 Suggestive evidence showed that lower albumin and higher direct bilirubin were associated with higher risk of COVID-19 hospitalization 59 but null associations for other liver function markers [alanine aminotransferase (ALT), alkaline phosphatase (ALP), aspartate aminotransferase (AST), γ-glutamyl transferase (GGT), indirect bilirubin, total bilirubin and total protein].…”
Section: Resultsmentioning
confidence: 99%
“…Ponsford MJ et al [ 16 ] reported no effect of LDL-C on COVID-19 with respiratory failure (OR, 0.85; 95% CI, 0.61–1.20) using GLGC GWAS data [ 44 ] and COVID-19 GWAS data involving 1610 cases with respiratory failure and 2205 controls in Italy and Spain [ 45 ]. Recently, Zhang et al [ 17 ] reported that Apo-B had a causal effect on COVID-19 susceptibility (OR, 1.18; 95% CI, 1.07–1.29; P = 0.001) using GWAS data of the Apo-B trait for 24,925 participants of European ancestry and UKBB data with 1221 COVID-19 cases and 4117 controls. However, they did not find any causal effect of Apo-B, LDL-C or TGs on COVID-19 severity (for Apo-B: OR, 0.95; 95% CI, 0.84–1.07; P = 0.36; for LDL-C: OR, 0.96; 95% CI, 0.85–1.09; P = 0.51; for TG: OR, 0.94; 95% CI, 0.78–1.15; P = 0.56) using LDL-C and TG traits GWAS for less than 300,000 participants of European ancestry and COVID-19 GWAS data obtained in Italy and Spain [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent genome-wide association study (GWAS) using UK Biobank (UKBB) data and MR analysis [ 13 ] reported that among atherogenic lipid-related traits (apolipoprotein B [Apo-B], low-density lipoprotein cholesterol [LDL-C], and triglyceride [TG]), Apo-B accounted for the causal effect on CAD risk, independently of LDL-C and TGs. Nevertheless, the estimated effects of atherogenic lipid-related traits on COVID-19 risk are inconsistent even among MR studies [ 14 17 ]. The aim of the present study was to estimate causal effects of serum Apo-B, LDL-C, and TG levels on risk of COVID-19 susceptibility, hospitalization, and severity in the European population using a two-sample MR approach.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Further study found that higher total cholesterol and ApoB levels might increase the risk of COVID-19 infection. [22] Many studies used BMI as an indicator of obesity, which means excessive body fat.…”
Section: Characteristics Of the Study Subjectsmentioning
confidence: 99%